2019
DOI: 10.1097/md.0000000000015986
|View full text |Cite
|
Sign up to set email alerts
|

Medical resource utilization and costs for intraoperative and early postoperative periprosthetic hip fractures following total hip arthroplasty in the medicare population

Abstract: This study assessed the impact of intraoperative and early postoperative periprosthetic hip fractures (PPHFx) after primary total hip arthroplasty (THA) on health care resource utilization and costs in the Medicare population. This retrospective observational cohort study used health care claims from the United States Centers for Medicare and Medicaid Standard Analytic File (100%) sample. Patients aged 65+ with primary THA between 2010 and 2016 were identified and divided into 3 groups – patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Cost parameters were derived from prior reports [10,13,22,39] (Table 1). The incremental direct and indirect costs associated with the direct anterior approach compared with the posterior approach were estimated from a financial analysis by Joseph et al [22].…”
Section: Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost parameters were derived from prior reports [10,13,22,39] (Table 1). The incremental direct and indirect costs associated with the direct anterior approach compared with the posterior approach were estimated from a financial analysis by Joseph et al [22].…”
Section: Costmentioning
confidence: 99%
“…They aggregated direct expenses, such as surgeon fees, implants, anesthesia and medications, as well as indirect expenses such as overhead, staff fixed salaries, space and lights. The cost of intraoperative fracture was derived from a study utilizing data from the US Centers for Medicare and Medicaid Services Standard Analytic File, which included data from Medicare Part A and Part B claims which captures Fee-for-service services [13]. Finally, the cost of revision THA was estimated based on a sample derived from the Premier Research Database, which includes clinical, demographic, and cost data from a large sample of general, non-federal, acute-care hospitals in the United States [10].…”
Section: Costmentioning
confidence: 99%
“…Periprosthetic fracture is a severe complication of total hip arthroplasty (THA) and is sometimes catastrophic. It has become a major reason for revision surgery, accounting for 6% of revisions recorded in registries in the United States and 20% in Australia 1 ; in particular, periprosthetic femoral fracture (PFF) is an increasingly prominent cause, resulting in poor clinical outcomes and high mortality rates 2–5 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the incidence of intraoperative periprosthetic femoral fractures (IPFFs) is not less than that of postoperative periprosthetic femoral fractures 6,7 . Fractures identified intraoperatively can be treated during primary surgery and have statistically significantly better treatment outcomes and a lower rate of catastrophic consequences than fractures identified postoperatively 2,7 . Those fractures that are undetected and untreated intraoperatively may result in delayed weight bearing and returning to normal activities, which sometimes need difficult and controversial management strategies and necessitate complicated and serious reoperations 8 .…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important since the number of complications following THA is predicted to increase with the rise in procedure volume. The majority of complications after THA can be avoided if they are foreseen and managed judiciously as they arise 4,8 .…”
mentioning
confidence: 99%